Open practices inpPublic higher education in Portugal: faculty perspectives - Cardoso, Paula (2019)
In recent years, the Open Educational Resources (OER) and Open Access (OA) movements have been essential in creating opportunities in all scholarly activities, within the context of higher education. The main purpose of this research was to understand how perceptions and practices of faculty towards OER are related to their perceptions and practices towards OA. It is an exploratory and descriptive study, with a mixed methods approach, undertaken in Portugal. Results indicate that, although faculty already show some degree of knowledge and use of OER and OA in their teaching and research practices, there is still a general lack of knowledge in both fields. However, the convergence of perceptions regarding both fields provide evidence on the possibility of a common approach to both fields in faculty’s educational practices, with the purpose of opening up their educational and scientific resources, thus reinforcing the principles of transparency, collaboration and openness to knowledge.